KELAYAKAN ISI DAN PENYAJIAN MATERI TEKS EKSPOSISI PADA BUKU TEKS SISWA BAHASA INDONESIA KELAS X SMA/SMK/MA KURIKULUM 2013 - Hasnah Setiani; Wagiran Wagiran; Ida Zulaeha (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The role of textbooks as the main source of learning in schools requires that the content and presentation be categorized as appropriate. The problem that arises in the use of learning textbooks is that the feasibility of the content and presentation of textbooks specifically on negotiating text material is not yet known. Reviewing the quality of content and presentation in learning textbooks is an urgency for learning at this time. The results of the quality of the content and presentation of textbooks are a consideration for educators in determining learning resources in the form of learning textbooks as well as being an evaluation for the government in developing student learning textbooks. This study aims to identify the feasibility of the content and presentation of negotiating text material in Indonesian language textbooks for class X SMA/SMK/MA. This study used qualitative research methods. The data collection technique in this study is the documentation technique. Qualitative analysis includes aspects of content feasibility and presentation using interactive model data analysis techniques by Miles and Huberman including four components of analysis namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research on the feasibility analysis of the contents and presentation of negotiating text material in class X Indonesian textbooks can be concluded that the textbooks obtained very good criteria for the content and presentation components. The score obtained for the content component shows 94% and the score obtained for the presentation component shows 97%.